Subspace exclusion zones for damage localization. (1st January 2019) - Bernal, Dionisio; Ulriksen, Martin D.
Highlights: A localization approach that allows for user-defined resolution is presented. Theoretically grounded on the fact that changes can be generated from boundaries of regions that contain the damage. Localization metric measures how well the changes can be justified from the postulated boundaries. Robustness can be promoted by aggregating results at different frequencies. Knowledge of input histories is not needed for some conditions - never for single source excitations. Abstract: If a subdomain of a structural system is introduced to a perturbation, the resulting shifts in any field quantity outside the boundary of some closed region encompassing the perturbation can be generated from stress fields acting on the aforementioned boundary. In the present paper, this is exploited in the context of structural damage localization to cast the Subspace Exclusion Zone (SEZ) scheme, which locates damage by inspecting the feasibility of generating the observed shifts from actions acting at the boundary of the postulated zones in a model of the structure in question. As such, the SEZ scheme is a forward interrogation that allows for a user-defined localization resolution and, under certain input conditions, operates without the use of system identification. The approach is most conveniently implemented in the Laplace domain and holds at s -values for which the load vector in the reference and the damaged states are proportional. The constraint that ensures exact results in an idealized model context is that the number of measurements outside any considered exclusion zone (EZ) exceeds the number of DOF on its boundary. It is shown, however, that useful results can be obtained with notably smaller sensor counts. The paper illustrates application of the SEZ scheme in simulations and in an experimental setting using a beam subjected to harmonic input.